Literature study The Effect of Benson Relaxation Therapy on Stress Levels in patients with hypertension - Linda Linda; Rohni Taufika Sari; Zaqyyah Huzaifah; Husna Widya Atma (OMNICODE Journal (Omnicompetence Community Developement Journal), 2022)
Benson relaxation is a treatment technique to relieve pain, insomnia (unable to sleep) or anxiety, namely combining progressive muscle relaxation techniques with religious relaxation to get maximum results (Benson, 2000 in Octavian, 2015). Benson's relaxation exercises have been shown to modulate stress related to conditions such as anger, anxiety, cardiac dysrrhythmias, chronic pain, depression, hypertension and insomnia and cause feelings of calmerness (Benson, 2000 in Dewi, 2014). Stress that is not immediately overcome can provoke the occurrence of hypertension. Purpose : The purpose of this literature study is to determine the effect of giving benson relaxation therapy on stress levels in people with hypertension. Technology data retrieval with PICOT analysis. Method: The design of this study used a literature study by examining 8 journals related to benson relaxation therapy. Data retrieval techniques with PICOT analysis. Results: Based on the analysis of journals related to researcher variables, results were obtained that there was an effect of giving benson relaxation therapy on stress levels in people with hypertension. Conclusion : It can be concluded that there is an influence of the administration of benson relaxation therapy on stress levels in people with hypertensi.